Hubungan Faktor Lingkungan Fisik dan Tindakan Masyarakat dengan Kejadian Demam Berdarah Dengue (DBD) di Wilayah Kerja Puskesmas Rawasari Kota Jambi Tahun 2025 - Annisa Aruna El Tivani; Oka Lesmana S.; Andree Aulia Rahmat; RD. Halim; Puspita Sari (Pusat Riset dan Inovasi Nasional, 2025)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus and transmitted by the Aedes aegypti mosquito. The working area of the Rawasari Health Center in Jambi City shows a trend of increasing dengue cases from year to year. This indicates that there may be other factors influencing the incidence of dengue, including physical environmental conditions and community behavior. The objective of this research is to determine the relationship between the presence of mosquito larvae in water reservoirs/containers, the action of hanging clothes, using mosquito repellent, cleaning water containers, disposing of waste items, and installing wire mesh with the incidence of dengue fever in the working area of the Rawasari Health Center in 2025. This research uses a quantitative study, with a case control design. The sample size consisted of 24 cases and 24 controls determined by matched case control study techniques based on age and gender. Data were collected through questionnaires and observation sheets, and analyzed using the chi-square test to determine the relationship between the independent variables and the incidence of dengue fever. The results show that the presence of mosquito larvae in water storage containers (p-value 0.042), practices of cleaning water storage containers (p-value 0.020), actions to eliminate waste items (p-value 0.043), and the installation of screens or mosquito nets (p-value 0.004) are significantly related to the incidence of dengue fever. Conversely, other factors such as the habit of drying clothes and the use of mosquito repellent did not show a statistically significant relationship with dengue fever cases in the study population. There is a significant relationship between the actions of cleaning water storage places and installing wire mesh. Effective prevention requires active community involvement in maintaining environmental cleanliness and consistently implementing the 3M Plus practices.